GREEN SYNTHESIS OF ZnO NANOPARTICLES FROM FOENICULUM VULGARE, ITS CHARACTERIZATION AND BIOLOGICAL POTENTIAL AGAINST BACTERIA - S. Khoso; S. Mehar; I. Anam; N. Naheed; F. Saeed; N. Khan; B. H. Abbasi (Journal of Animal and Plant Sciences, 2022)
The present research deals with synthesis, characterization, and biological potential of Foeniculum vulgare mediated zinc oxide nanoparticles (ZnO NPs). Extract of Foeniculum vulgare (a medicinal plant) was used to synthesize nanoparticles by reaction of extract with Zinc acetate (2M) solution. Synthesized ZnO Nps were characterized by various advance techniques such as FTIR, SEM, EXD, SEM and XRD. Debye–Scherrer equation (D = kλ / β θ cos) was used to calculate mean diameter of synthesized Nps utilizing XRD technique. Formation of ZnO Nps was confirmed by SEM analysis of resultant white colored stable Nps of reaction. The size of synthesized Nps was determined by SE technique which was found to be 22.94 nm. Phytochemical analysis reveals high content of secondary metabolites in NPs as compare to crude extract. The plant was observed with high content of flavonoids followed by phenolic compounds and then alcoholic compound. Order of different phytochemical was found to be flavonoids > Phenolic compound > alcoholic compounds. Plant’s crude extract and plant mediated ZnO Nps were analyzed for biological potential with refence of antibacterial and antioxidant analysis. DPPH and TRP test were performed for antioxidant potential which showed positive response while antibacterial potential was evaluated by well diffusion method. Significant antibacterial potential was observed against Escherichia coli and Staphylococcus aureus bacterial strain. However, plant mediated ZnO NPs were not observed with potential to kill population of Listeria monocytogenes bacterial specie.
Keywords: Medicinal Plants; Foeniculum vulgare; ZnO Nps; antibacterial activity